start by distributing the negative sign
how do i do that
hint: -(A-B-C) = -A+B+C
oh ok gotcha
-(3x^2-4x-3) = ?
almost, check your signs
-(-4x) = ? -(-3) = ?
4x and 3!
right, so we have - 3x^2 + 4x + 3 on the right side after we distribute now we put the whole problem back together
x^2-4x+3- 3x^2 + 4x + 3 know where to go from here?
just combine right?
yes, so what does that give us?
x^2+14-3x^2? Im really bad at combining like terms for some reason..
i most likely did it wrong
not quite x^2 - 3x^2 = ?
so it would be x^+11?
uh, not quite hint: 1 - 3 = -2 x - 3x = -2x x^2 - 3x^2 = ?
don't forget the x^2
im so bad at this one ...
nope, when you combine like terms, you keep the variable x^2 - 3x^2 = -2x^2
plus 6 right?
think of it this way: 1 - 3 = -2 1 dollar - 3 dollars = -2 dollars the "dollar" stays in the answer, just like x^2 stays in the answer
so our final answer is -2x^2 + 6
ok, im gonna need to practice that one a bit. thanks for all of you help! is it ok if i tag you in a couple of questions tomorrow?
sure, I'm online all day tomorrow
ok- thanks i will tag you !